(untitled) (UUM Journal of Legal Studies, 2026)
Digital labour platforms have emerged as a solution to unemployment issues around the world over the past decade. The flexibility and independence offered on digital labour platforms have attracted workers to perform gig work on digital platforms. Issues such as unfair payment systems and unjust terminations of contracts by platform providers have affected the sustainability of digital labour platforms in Malaysia. This study aims to achieve two research objectives. The first is to examine the labour rights issues surrounding platform workers. Canada has taken immediate steps to enact a statute and has amended its existing legislation to ensure its platform workers are protected. Therefore, the second objective of this study is to analyse how Canada provides labour protection for the country’s platform workers. The objectives of this study are achieved through adopting a qualitative method by way of content analysis of journal articles and relevant government statutes. Semi-structured interviews with relevant ministries and government agencies were conducted, and the results were analysed. A comparative analysis method was used to compare the legislative frameworks in Malaysia and Canada. It is suggested that Malaysian policymakers should refer to the Digital Platform Workers’ Rights Act 2022 (DPWRA) and the Employment Standards Act 2000 (ESA) in formulating protection for platform workers. This study underlines the urgent need for integrated policy reforms to ensure fair and sustainable digital labour practices in Malaysia.